Routine screening for SARS CoV-2 in unselected pregnant women at delivery - Díaz-Corvillón, Pilar (PLoS One, 2020)
BACKGROUND: South America has become the epicenter of coronavirus pandemic. It seems that asymptomatic population may contribute importantly to the spread of the disease. Transmission from asymptomatic pregnant patients’ needs to be characterized in larger population cohorts and symptom assessment needs to be standardized. OBJECTIVE: To assess the prevalence of SARS CoV-2 infection in an unselected obstetrical population and to describe their presentation and clinical evolution. METHODS: A cross-sectional study was designed. Medical records of pregnant women admitted at the Obstetrics & Gynecology department of Clínica Dávila for labor & delivery, between April 27(th) and June 7(th), 2020 were reviewed. All patients were screened with RT-PCR for SARS CoV-2 at admission. After delivery, positive cases were inquired by the researchers for clinical symptoms presented before admission and clinical evolution. All neonates born from mothers with confirmed SARS CoV-2 were isolated and tested for SARS CoV-2 infection. RESULTS: A total of 586 patients were tested for SARS CoV-2 during the study period. Outcomes were obtained from 583 patients which were included in the study. Thirty-seven pregnant women had a positive test for SARS CoV-2 at admission. Cumulative prevalence of confirmed SARS CoV-2 infection was 6.35% (37/583) [CI 95%: 4.63–8.65]. From confirmed cases, 43.2% (16/37) were asymptomatic. From symptomatic patients 85.7% (18/21) had mild symptoms and evolved without complications and 14.3% (3/21) presented severe symptoms requiring admission to intensive care unit. Only 5.4% (2/37) of the neonates born to mothers with a positive test at admission had a positive RT-PCR for SARS CoV-2. CONCLUSION: In our study nearly half of pregnant patients with SARS CoV-2 were asymptomatic at the time of delivery. Universal screening, in endemic areas, is necessary for adequate patient isolation, prompt neonatal testing and targeted follow-up.